MATHEMATICAL MODELING AND SIMULATION OF CO2 REMOVAL FROM AN ALKALINE SOLUTION FOR FUEL CELLS APPLICATIONS - Sapucaia, M. B. R.; Jacob-Furlan, B.; Gonçalves, R. S. R.; Balmant, W.; Martins, L. S. (Revista de Engenharia Térmica, 2023)
In order to reduce oil dependency and reduce CO2 emissions stabilizing the greenhouse effect on the planet, the search for new renewable energy sources has been intensified, with a particular interest in hydrogen based solutions. Hydrogen can be used in fuel cells, which have several applications. Fuel Cells are among the environmentally friendly energy conversion systems for the 21st century with simple components such as membrane, catalyst, rearrangeable configurations that allow them to accommodate space limitations, and their use of hydrogen and oxygen. There are many types of fuel cells that are distinguished by the electrolyte type and their operating temperature. Alkaline Membrane Fuel Cells (AMFCs) and Proton-Exchange Membrane Fuel Cells (PEMFCs) are major types that work in low temperatures and produce only H2O and electricity as part of the electrochemical reaction. AMFC is a fuel cell that has more affordable membranes, when compared to the PEMFC that uses a polymeric membrane with high cost, making applications more expensive. In AMFCs, the alkaline membrane used, is a simple filter paper saturated with KOH solution that allows ions to pass through the membrane, however, suffers CO2 poisoning when it gets in contact to the carbon dioxide present in the air, reacting in the KOH and capturing hydroxyl ions. The poisoning will generate chemical compounds that will interfere with the energy generation and efficiency of the fuel cell. The main cause of the decreasing performance of carbonate formation is the precipitation of large metal carbonate crystals such as K2CO3 and the formation of H2O in the membrane, decreasing KOH concentration. If not addressed, this issue will limit the use of AMFC to pure oxygen applications only, instead of the air itself, which restricts the applicability of the technology. This study presents a mathematical model of a purifier that reduces the concentration of CO2 present in the air, improving conditions to be used in AMFC for mobile applications as automotive vehicles and without the need to use pure oxygen.